(untitled) (Scientific journal of the Fergana State University, 2023)
This article is about the development of media literacy in the information society. Scientific definitions of media literacy and its necessity today are revealed. Based on pedagogical data, the author studied and analyzed specific aspects of media literacy development in the information society based on existing scientific literature.